Effects of RhoA and RhoC upon the sensitivity of prostate cancer cells to glutamine deprivation. (2nd January 2021) - Bueno De Paiva, Luciana; Aline Bernusso, Vanessa; Machado-Neto, João Agostinho; Traina, Fabiola; Ridley, Anne J; Olalla-Saad, Sara Teresinha; Lazarini, Mariana
ABSTRACT: RhoA and RhoC contribute to the regulation of glutamine metabolism, which is a crucial determinant of cell growth in some types of cancer. Here we investigated the participation of RhoA and RhoC in the response of prostate cancer cells to glutamine deprivation. We found that RhoA and RhoC activities were up- or downregulated by glutamine reduction in PC3 and LNCaP cell lines, which was concomitant to a reduction in cell number and proliferation. Stable overexpression of wild type RhoA or RhoC did not alter the sensitivity to glutamine deprivation. However, PC3 cells expressing dominant negative RhoA N19 or RhoC N19 mutants were more resistant to glutamine deprivation. Our results indicate that RhoA and RhoC activities could affect cancer treatments targeting the glutamine pathway.